Jackfruit seeds milk administration increased hemoglobin levels in third trimester pregnant women at Bangetayu Health Center, Semarang, Indonesia - Meiranny, Arum; Yumna, Jihan Diya; Jannah, Muliatul (Universitas Airlangga, 2024)
HIGHLIGHTS Pregnant women are prone to suffer from anemia. Jackfruit seeds milk can be consumed as a non-pharmacological treatment to prevent and overcome anemia in pregnant women. ABSTRACT Objective: This study aimed to investigate the impact of administering jackfruit seeds milk on hemoglobin levels in third trimester pregnant women at Bangetayu Health Center in Semarang, Indonesia. Materials and Methods: This study utilized a quasi-experimental approach with pre- and post-test control groups. The study included a sample of 35 out of 107 third trimester pregnant women from the Bangetayu Health Center in Semarang, Indonesia. The study was conducted between January and February 2022. The research sample comprised 35 respondents, divided into 17 control groups and 18 intervention groups. Purposive sampling was utilized as the sample technique. Data analysis involved both univariate and bivariate analysis techniques. The analysis involved utilizing chi-square test and independent t-test. This study utilized the SPSS software version 23 for data analysis. Results: The intervention group had an average hemoglobin level of 10.2 g/dL before treatment and 10.7 g/dL after therapy. The average hemoglobin level in the control group increased from 12.1 g/dL before to 12.4 g/dL after. The results indicated a p-value of 0.000 and a Relative Risk (RR) of 1.2. Conclusion: The consumption of jackfruit seed milk had an effect on the hemoglobin levels of third-trimester pregnant women at the health center in Bangetayu, Semarang, Indonesia. Failure to consume jackfruit seed milk results in 1.2 times decrease in the likelihood of boosting hemoglobin levels.